MODUL LATIH MODBUS RS – 485 - Anwar Anwar; Hendrayudi Hendrayudi; Gugun Rahmattulah; Tiara Eka (Jurnal Poli-Teknologi, 2017)
ABSTRACTThis training module explains about application system which integration between PLC (Programmable Logic Controller), HMI (Human Machine Interface), and Variable Frequency Drive for controlling the speed of motor using protocol communication. The proccess of controlling system is PLC, and Variable Frequency Drive as a regulator of speed motor. Dispostion of speed motor is determined by Ladder Diagram PLC with function block communication and the data is sent by protocol communication. The communication between PLC and Variable Frequency Drive has function for writing and reading data or the status of work from Variable Frequency Drive. Data of Variable Frequency Drive will be copied to memory of PLC and then it will use for monitoring by HMI.Keywords : Function Block Communication, Setting Communication of Modbus, The Program of PLCABSTRAKModul latih ini menjelaskan tentang aplikasi sistem yang terintegrasi antara PLC (Programable Logic Controller), HMI (Human Machine Interface) dan Inverter dengan mengatur kecepatan motor menggunakan komunikasi modbus protocol. Sistem pengendali proses dalam sistem ini adalah PLC dan Inverter adalah sebagai pengatur kecepatan motor. Pengaturan kecepatan motor ditentukan berdasarkan pemrograman PLC yang dibuat dengan ladder diagram menggunakan blok fungsi komunikasi dan datanya dikirim melalui komunikasi protocol. Komunikasi antara PLC dan Inverter berfungsi untuk menulis dan membaca data-data atau status kerja dari inverter. Data-data inverter akan disalin kedalam memori PLC yang selanjutnya akan digunakan untuk proses monitoring oleh HMI.Kata kunci: Pemrograman PLC, Setting komunikasi modbus, Blok fungsi komunikasi